Analisis Kekuatan Desain Velg Kendaraan Ringan Menggunakan Metode Elemen Hingga: Pendekatan Inovatif untuk Keamanan dan Efisiensi - Putra, Agus Dwi; Diama Rizky Septiawan; Muhammad Arif Nur Huda; Dewi Izzatus Tsamroh; Bella Cornelia Tjiptady (Badan Kerja Sama Teknik Mesin Indonesia, 2025)
Car wheels are critical components responsible for bearing vehicle loads and ensuring stability during driving. This study aims to analyze the strength of car wheels using the Finite Element Method (FEM) with Solidworks 2020 software. The analyzed parameters include von mises stress, equivalent strain, displacement, and safety factor. Simulation results show a maximum stress of 1.978 × 10⁵ N/m² and a maximum strain of 2.449 × 10⁻⁶, within the safe limits of aluminum alloy material. A maximum displacement of 5.687 × 10⁻⁴ mm indicates sufficient structural stiffness of the wheel. The minimum factor of safety, 1.087 × 10³, suggests a high tolerance against failure. This study confirms that the wheel design is safe, efficient, and meets safety standards. The finite element method effectively identifies critical areas and optimizes the design before production. Validation through physical testing is recommended to ensure alignment with real-world conditions.